Expression of Cathepsins B, D, and G in Isocitrate Dehydrogenase-Wildtype Glioblastoma - Koh, Sabrina P.; Wickremesekera, Agadha C.; Brasch, Helen D.; Marsh, Reginald; Tan, Swee T.; Itinteang, Tinte (Frontiers in Surgery, 2017)
Aim: To investigate the expression of cathepsins B, D and G, in relation to the cancer stem cell (CSC) subpopulations we have previously characterized within isocitrate dehydogenase (IDH)-wildtype glioblastoma (IDHWGB). Methods: 3,3-Diaminobezidine (DAB) immunohistochemical (IHC) staining for cathepsins B, D and G, was performed on 4µm-thick formalin-fixed paraffin-embedded IDHWGB samples obtained from six patients. Two representative GBM samples from the original cohort of patients were selected for immunofluorescent (IF) IHC staining, to identify the localization of the cathepsins in relation to the CSC subpopulations. NanoString gene expression analysis and colorimetric in-situ hybridization (CISH) were conducted to investigate the transcriptional activation of genes encoding for cathepsins B, D and G. Data obtained from cell counting of DAB IHC-stained slides and from NanoString analysis were subjected to statistical analyses to determine significance. Results: Cathepsin B and cathepsin D were detected in IDHWGB by DAB IHC staining. IF IHC staining demonstrated expression of both cathepsin B and cathepsin D by the OCT4+ and SALL4+ CSC subpopulations. NanoString gene analysis and CISH confirmed the abundant transcript expression of these cathepsins. The transcriptional and translational expression of cathepsin G was minimal and was confined to cells within the microvasculature. Conclusion: This study demonstrated the expression of cathepsin B and cathepsin D but not cathepsin G within the CSC subpopulations of IDHWGB at both the transcriptional and translational level. Cathepsin G was expressed at low levels and was not localized to the CSC population of IDHWGB. The novel finding of cathepsin B and cathepsin D in IDHWGB suggests the presence of bypass loops, which may facilitate the production of angiotensin peptides. Elucidating the precise role of these cathepsins may lead to better understanding and more effective treatment of this aggressive tumor.